Optimizing the Timeframe to Produce Polychaetes (Hediste diversicolor) Enriched With Essential Fatty Acids Under Different Combinations of Temperature and Salinity - Jerónimo, Daniel; Lillebø, Ana Isabel; Rey, Felisa; Ii, Henrique Koga; Domingues, M. Rosário M.; Calado, Ricardo (Frontiers in Marine Science, 2021)
Polychaetes can be successfully employed to recover essential fatty acids (EFA) from wasted uneaten aquafeeds present in aquaculture effluents. The optimization of the timeframe required to produce premium ragworms (Hediste diversicolor) biomass rich in EFA is paramount to make available to the aquafeeds industry another alternative ingredient to fish meal and fish oil. The present study aimed to evaluate the potential enrichment of ragworms fatty acid (FA) profile when fed a commercial aquafeed during 10, 20, and 40 days (D10, D20, and D40) under different combinations of water temperature (20 and 25°C) and salinity (15, 20, and 25). Total FA incremented progressively overtime, with D40 polychaetes exhibiting average values ranging between 70 and 90 μg mg–1 DW. The average values of n-6 FA ranged between 13 and 17 μg mg–1 DW, while that of n-3 FA varied between 17 and 19 μg mg–1 DW at D40. No significant differences were found in the FA profile of H. diversicolor cultured under different combinations of temperature and salinity. The FA profile of cultured polychaetes exhibited between 28 and 31% dissimilarity from that of wild conspecifics and displayed a higher content of two essential n-3 FA: eicosapentaenoic (20:5 n-3, EPA) and docosahexaenoic acids (22:6 n-3, DHA) (values ranging between 9.6–11.2% and 4.3–5.0% of total FA, respectively). A higher similarity in FA profile was recorded between D40 polychaetes and aquafeed than with initially stocked or wild specimens. Palmitic (16:0), oleic (18:1 n-9), linoleic (18:2 n-6), eicosadienoic (20:2 n-6), EPA (20:5 n-3), and DHA (22:6 n-3) were the FA whose concentration exhibited the highest increment. Evidence of de novo FA biosynthesis was observed through the formation of some FA that were neither present in the initially stocked biomass, nor in the aquafeed supplied, such as 5,11-eicosadienoate (Δ5,1120:2), 7,13,16-docosatrienoate (Δ7,13,1622:3), dihomo-gamma-linolenic (20:3 n-6), eicosatrienoic (20:3 n-3) and eicosatetraenoic (20:4 n-3) acids. A plateau of total FA, n-6, and n-3 FA was not reached over the study period. Overall, the present study highlights the potential of H. diversicolor as an extractive species for integrated multi-trophic aquaculture (IMTA) applications.